Comprehensive Analysis of Alternative Polyadenylation Events Associated with the Tumor Immune Microenvironment in Colon Adenocarcinoma - Pang, Fangning; Yang, Peng; Wang, Tongfei; Li, Xuzhao; Wu, Xiaoyong; Yue, Rong; Bai, Bin; Zhao, Qingchuan (Current Genomics, 2023)
Objective: Colon adenocarcinoma (COAD) is one of the leading causes of cancer death worldwide. Alternative polyadenylation (APA) is relevant to the variability of the 3'-UTR of mRNA. However, the posttranscriptional dysregulation of APA in COAD is poorly understood. Methods: We collected APA data from The Cancer Genome Atlas (TCGA) COAD (n =7692). APA events were evaluated using PDUI values, and the prognostically significant APA events were screened by LASSO Cox regression to construct a prognostic model. Then, prognostic model functions and possible regulatory genes of characteristic APA events were analyzed. Finally, the immune regulatory network based on APA regulatory genes was analyzed and established. Results: A total of 95 APA events were found to influence the COAD outcomes. Among them, 39 genes were screened as characteristic prognostic APA events by LASSO Cox regression to construct a COAD prognostic signature. The analysis results suggested that a high signature score was associated with poor prognosis and was significantly correlated with a variety of immune cells, including NK and Th1, 2 and 17 cells. Further analysis showed that APA regulators mainly served roles in the prognosis of COAD. Based on the above results, we constructed an immunoregulatory network for APA regulatory genes-APA genes-immune cells. Conclusion: Our study revealed that APA events in COAD may regulate tumor progression by influencing immune cells, which provides a new direction for exploring the influencing mechanism of the tumor immune microenvironment and is expected to provide a potential new target for COAD immunotherapy.
Keywords: immunity